2018
DOI: 10.1371/journal.pone.0203500
|View full text |Cite
|
Sign up to set email alerts
|

Family and the field: Expectations of a field-based research career affect researcher family planning decisions

Abstract: Field-based data collection provides an extraordinary opportunity for comparative research. However, the demands of pursuing research away from home creates an expectation of unburdened individuals who have the temporal, financial, and social resources to conduct this work. Here we examine whether this myth of the socially unencumbered scholar contributes to the loss of professionals and trainees. To investigate this, we conducted an internet-based survey of professional and graduate student anthropologists (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
(45 reference statements)
1
31
0
1
Order By: Relevance
“…Studies have shown that social background affects individual educational attainments, implying that parental (notably cultural) capital is a reliable predictor of academic success [13]. Accordingly, young students, who are familiar with rules of the academic field (e.g., colleges and universities), may devise strategies that would assist them in acting–and succeeding—within it [55]. Studying abroad, for example, is a valuable expression of having a ‘feel for the game’ in this specific field [56, 57], ‘an element of the academic habitus’ ([21], p. 87), that advances mobility in the field.…”
Section: Academic Mobilitymentioning
confidence: 99%
“…Studies have shown that social background affects individual educational attainments, implying that parental (notably cultural) capital is a reliable predictor of academic success [13]. Accordingly, young students, who are familiar with rules of the academic field (e.g., colleges and universities), may devise strategies that would assist them in acting–and succeeding—within it [55]. Studying abroad, for example, is a valuable expression of having a ‘feel for the game’ in this specific field [56, 57], ‘an element of the academic habitus’ ([21], p. 87), that advances mobility in the field.…”
Section: Academic Mobilitymentioning
confidence: 99%
“…Recent research shows that women's academic careers are more negatively affected by family concerns than are men's; relatively fewer women are at the highest ranks, and they are much less likely than men to be married or to have children (Mason et al, ). This has more recently been documented specifically in fieldwork‐based anthropology (Lynn et al, ).…”
Section: Documented Treatment Based On Gendermentioning
confidence: 89%
“…Documenting these women's experiences adds historical context to continued gender inequality in physical anthropology (Turner et al, ). This manifests today as women being underrepresented in faculty positions relative to the numbers of women in the field (Antón et al, ; Turner, ), prematurely stopped or delayed in career advancement (Turner et al, ), more likely than men to experience harassment (Clancy et al, ), having careers that are disproportionately affected by family responsibilities (Lynn et al, ), and being under‐recognized for their professional contributions (Isbell et al, ). Promisingly though, increasing numbers of women hold tenure track positions, the immediate past four presidents of the AAPA have been women, and organizations such as the Committee on Diversity Women's Initiative have formed with the purpose of prioritizing the retention and advancement of women in anthropology (Turner et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is worse in a field discipline such as archaeology since research, teaching, and professional development are frequently linked to fieldwork undertaken at some distance from both office and family home. Indeed, a study of anthropologists and fieldwork found higher levels of stress due to an imbalance between career and family alongside gender inequities and intersectionality (Lynn, Howells & Stein 2018).…”
Section: Always-on Scholarshipmentioning
confidence: 99%